Sign Languages - Leeson, Lorraine (Council of Europe and European Centre for Modern Languages (ECML), 2019)
In 2018, the Parliamentary Assembly of the Council of Europe passed a resolution on Sign Languages (Resolution 2247). This recognises the thirty plus indigenous sign languages of Europe as natural languages but also acknowledges that few states have recognised sign languages as official languages to date (See also Wheatley and Pabsch 2012 for an overview on sign language recognition in Europe). As a result, access to education and public services using sign languages remains limited. The challenges faced in acquiring a sign language as a first language, learning it as a second or subsequent language, or accessing information through sign languages are well documented. Most recently, the Ministry of Foreign Affairs, Finland, published a report that looks at sign language rights within the framework of the Council of Europe and its member states (Tupi 2019), noting that sign language issues tend to be viewed via a disability lens, rather than seen from a cultural and linguistic perspective.
Changing contexts, evolving competences: 25 years of inspiring innovation in language education
PUBLISHED
Graz, Austria
Keywords: Sign language; Europe; Education; Digital Humanities; Identities in Transformation; Inclusive Society; Common European Framework of Reference for Languages (CEFR); European Language Portfolio; European Language Portfolio for Sign Languages (ELP-SL); Second Language Second Modality learning (L2M2); plurilingualism; sign language teaching and learning; Hearing impairment; Accessibility; Community; Communication; Culture; Deaf/Deafness; Education